Corporate Marketing and Innovation Strategies Based on Brand Management - Wu, ZiCheng (Transactions on Economics, Business and Management Research, 2024)
In a highly competitive business environment, effective brand management is crucial. A brand is not only a symbol of products and services, but also an external manifestation of corporate culture and values. A successful brand can evoke emotional resonance among consumers and establish long-term trust. Marketing, as a key component of brand development, directly impacts brand recognition and reputation through strategic planning and implementation. Initially, enterprises should focus on market positioning by conducting thorough preliminary research to understand market demands and competitive dynamics, thereby identifying a target market that aligns with their unique characteristics. Today, brand communication channels are diverse, allowing companies to convey their values to consumers in various ways and establish a positive brand image. Furthermore, leveraging the advantages of the internet and social media platforms through precise data analysis can help businesses quickly grasp consumer needs, adopt personalized marketing approaches, and enhance their market competitiveness, thereby generating greater economic benefits for the company.